DOPING GRAPHENE OKSIDA MENGGUNAKAN BORIC ACID (H2BO3) UNTUK MENINGKATKAN KINERJA COIN CELL SUPERKAPASITOR - Nurlia Sari; Andita Ganda (Jurusan Teknik Mesin Universitas Negeri Surabaya, 2020)
Boron doped in graphene oxide is a convincing method for modifying the properties of electrons in supercapacitors. In this study, we compared the performance of graphene electrode supercapacitor coin cells and boron-doped graphene. Graphene oxide was made by the modified Hummers method, followed by the boron-doped process by adding boric acid chemicals then continued with the pyrolysis process in the argon and hydrogen atmosphere at high temperatures. The precursors then used as electrodes (anodes and cathodes) in supercapacitor coin cells. The results show that the addition of boron dopants to graphene results in lower electrolyte absorption at the beginning of the test, causing the specific capacity at the beginning tends to be low but more stable, whereas at the end of the test the specific capacity of boron dopants tends to be higher than graphene without dopants. The addition of Boron Dopants to Graphene is effective in its application in supercapacitor coin cells making it promising in future energy storage needs.